Effects of cytokine signaling inhibition on inflammation-driven tissue remodeling - Rebecca Bignold; Jill R. Johnson (Elsevier, 2021)
Fibrosis is a common condition that can affect all body tissues, driven by unresolved tissue inflammation and resulting in tissue dysfunction and organ failure that could ultimately lead to death. A myriad of factors are thought to contribute to fibrosis and, although it is relatively common, treatments focusing on reversing fibrosis are few and far between. The process of fibrosis involves a variety of cell types, including epithelial, endothelial, and mesenchymal cells, as well as immune cells, which have been shown to produce pro-fibrotic cytokines. Advances in our understanding of the molecular mechanisms of inflammation-driven tissue fibrosis and scar formation have led to the development of targeted therapeutics aiming to prevent, delay, or even reverse tissue fibrosis. In this review, we describe promising targets and agents in development, with a specific focus on cytokines that have been well-described to play a role in fibrosis: IL-1, TNF-α, IL-6, and TGF-β. An array of small molecule inhibitors, natural compounds, and biologics have been assessed in vivo, in vivo, and in the clinic, demonstrating the capacity to either directly interfere with pro-fibrotic pathways or to block intracellular enzymes that control fibrosis-related signaling pathways. Targeting pro-fibrotic cytokines, potentially via a multi-pronged approach, holds promise for the treatment of inflammation-driven fibrotic diseases in numerous organs. Despite the complexity of the interplay of cytokines in fibrotic tissues, the breadth of the currently ongoing research targeting cytokines suggests that these may hold the key to mitigating tissue fibrosis and reducing organ damage in the future.